Field experimental study on ground treatment of high fill embankments over expansive soils - Bin Hou; Faning Dang; Weihua Ding; Haibin Xue; Hong Zhan (Scientific Reports)
Abstract In valley regions where high-fill embankments are constructed, inadequate foundation bearing capacity is a frequently encountered challenge. At the Ankang Airport relocation site, expansive soils primarily originating from the Upper to Middle Pleistocene are widely distributed, which introduces substantial safety concerns for the stability of high-fill embankments. Prior to large-scale filling, a field experimental site was selected within the project area to conduct in-situ tests for ground improvement. Two ground reinforcement techniques—dynamic compaction and gravel pile compaction using driven casing—were implemented and assessed. Evaluations of physical and mechanical properties, including plate load and standard penetration tests (SPT), were carried out before and after the improvement procedures. Test results showed that the natural foundation soil had a characteristic bearing capacity of 260 kPa. Among the applied techniques, dynamic compaction replacement proved most effective, enhancing the bearing capacity to 580 kPa. However, due to the complex stratigraphy and shallow bedrock in certain zones, dynamic compaction may negatively impact bedrock stability. Numerical modeling further validated that dynamic compaction replacement induced the smallest settlement deformation. Targeted solutions were proposed in response to the issues identified during testing, offering practical guidance for similar foundation treatments in high-fill embankments over expansive soils.